Towards safe and stable Clostridium botulinum strains for research and industrial applications - Groothuis, Daphne (2022)
The pathogen Clostridium botulinum has gained significant infamy as the causative agent of botulism, a rare but potentially fatal paralytic condition. Unfortunately, research on these dangerous pathogens is limited due to the necessary high containment facilities and their associated costs. Therefore, the initial aim of this project was to develop a strategy, applicable to all members of the highly diverse C. botulinum family, to efficiently generate non-toxigenic strains, which would allow the expansion of the C. botulinum research scope. These highly desired surrogate strains are anticipated to find wide application in both industrial and research settings. In this context, ‘safe’ C. botulinum ATCC 3502 strains were created by deleting the neurotoxin gene using various technologies. However, the project took an unexpected turn when the unstable nature of this widely studied C. botulinum model strain was discovered. The cause of the ATCC 3502 mutator phenotype was pinned down via whole genome comparisons and was experimentally confirmed to be due to a partial, in-frame deletion of the mutL gene. Interestingly, several other group I strains bearing a similar genetic background were identified, which are, probably, also mutators. It is quite surprising that this is the first study revealing the rapid degeneration of strains of this organism, despite them being extensively investigated by different research groups. Evidently, these findings might have a significant impact on our current understanding of C. botulinum, affecting both the industrial and scientific community. In view of this finding, previously published results with this organism should henceforth be considered with caution. To pursue the initial aim of this thesis, similar C. botulinum family members were acquired and characterised. Various strategies to circumvent their restriction barriers, which hindered reliable and efficient DNA transfer, were successfully employed. Additionally, the effectiveness of a comprehensive donor customisation pipeline for improving DNA transfer efficiencies in previously ‘untouched’ strains is exemplified. Subsequently, empowered by CRISPR/Cas9 technology, different non-toxigenic strains were created and phenotypically assessed. Overall, the advancements presented here constitute a solid basis for the future generation of any desired safe C. botulinum strain.